Justification of the possibility of preserving buckwheat starter by cryopreservation method - Igonina E. D.; Chernova A. V.; Kazimirchenko O. V. (Vestnik MGTU)
High bioavailability of nutrients (micro- and macronutrients), improved taste and aroma of baked goods, long shelf life of products are the advantages of using starter cultures in production. The study provides a rationale for the cryopreservation periods for buckwheat flour starter, and defines the phases of the propagation and production cycle of the developed starter. The recommended fermentation temperature is 27 ± 1 °C, holding time is 5 hours, lifting force is 30 minutes, acidity is 10 ± 1 degrees. The composition of the starter microflora is represented by strains of Lactobacillus plantarum, Lactobacillus brevis bacteria in combination with strains of Candida milleri and Saccharomyces cerevisiae yeast. This microbiocenosis is preserved when transferring rice starter to buckwheat flour. Analysis of changes in the microflora composition and physicochemical parameters of the starter during storage at a temperature of –18 °C indicates that all parameters are within the normalized values by the end of the fourth week of storage. Starting from the sixth week, the amount of lactic acid microflora decreases, yeast cells grow; the lifting power of the starter reaches 40 minutes, the acidity decreases to 7 degrees. Thus, shock-frozen buckwheat starter is recommended to be stored at a temperature of –18 °C for 4 weeks, which is confirmed by the research results.